SOLVING OPTIMAL GENERATION DISPATCH PROBLEM IN POWER NETWORKS THROUGH PSO AND LAMBDA ITERATION TECHNIQUES (Nigerian Journal of Technology, 2018)
Efficient solution to the problem of economic dispatch of network generators has been a growing concern to power system utilities in recent times. This is aimed at determining the optimal allocation of the total network demand among the available generating units such that the total cost of generation is reduced while maintaining an acceptable generation output subject to specified system constraints. This paper, therefore, attempts to resolve this issue from two main perspectives; Lambda Iterative-based approach and Particle Swarm Optimization (PSO) technique. The theoretical backgrounds as well as the mathematical formulations for the two approaches are presented. The standard IEEE 14-Bus, IEEE 30-Bus and the Indian 62-Bus networks are used as case studies to present illustrative examples for the approach. The simulation results obtained using the two approaches are presented and compared. The comparisons of the results obtained show that the two approaches are suitable for providing efficient solutions to economic dispatch problems in large power networks. Keywords: economic dispatch; network demands; lamda iterative; particle swarm optimization;generation cost http://dx.doi.org/10.4314/njt.v38i1.21